ANALISIS PENERIMAAN PBB KABUPATEN / KOTA PROVINSI JAWA TENGAH PERIODE 2009 - 2013 (Jurnal Mahasiswa Pasca Sarjana, 2015)
The objectives of this research is to know  the impact of the Selling Value of Tax Object and the change of Tax Object to the Domestic Product of Regional Bruto in Central Java Province. Then this research also to know the  impact of the Selling Value of Tax Object, the change of Tax Object  and Domestic Product of Regional Bruto to the acceptance of Land and Building Tax in Central Java Province. This research take data from  35 District/City on the period 2009-2013. Then the data analyzed by panel data regression technique. This research found that the Selling Value of Tax Object  has a significant positive effect  to the Domestic Product of Regional Bruto and the Change of Tax Object has significant positive effect on Domestic Product of Regional Bruto. the Selling Value of Tax Object, Change of Tax Object and   Domestic Product of Regional Bruto partially have a significant  positive effect to the acceptance of Land and Building Tax. But Domestic Product of Regional Bruto  is not the intervening variable on the relationship between Change of Tax Object and the acceptance of Land and Building Tax. Keyword : The Selling Value of Tax Object, the Change of Tax Object, Domestic Product of Regional Bruto and the acceptance of Land and Building Tax